Analysis of Time Course and Dose Effect From Metformin on Body Mass Index in Children and Adolescents - Wang, Dong-Dong; Mao, Yi-Zhen; He, Su-Mei; Chen, Xiao (Frontiers in Pharmacology, 2021)
The purpose of this study was to analyze the time course and dose effect from metformin on body mass index (BMI) in children and adolescents by model-based meta-analysis (MBMA). Searching randomized controlled trial (RCT) studies of metformin on BMI in children and adolescents. The change rates of BMI from baseline values were used to evaluate metformin efficacy indicator. A total of 18 RCT studies, 1228 children and adolescents, were included for analysis, including patients with obesity, patients with type 1 diabetes mellitus, patients with nonalcoholic fatty liver, patients with precocity. In order to achieve better effect of metformin on BMI in children and adolescents, the present study recommended that for patients with obesity, 1000 mg/day metformin was required for at least 15.2 weeks, and 60.8 weeks to achieve the plateau of metformin effect; For patients with type 1 diabetes mellitus, 1000 mg/day metformin was required for at least 25.2 weeks, and 100.8 weeks to achieve the plateau of metformin effect; For patients with nonalcoholic fatty liver, 1000 mg/day metformin was required for at least 6.57 weeks, and 26.28 weeks to achieve the plateau of metformin effect; For patients with precocity, 425 mg/day metformin was required for at least 12.4 weeks, and 49.6 weeks to achieve the plateau of metformin effect. It was the first time to analyze the time course and dose effect from metformin on BMI and to recommend dosage and duration of treatment for metformin in children and adolescents with different disease types.